2007
DOI: 10.1021/jp072020u
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Study on the Solvation of N,N-Dimethyl-p-nitroaniline in Room-Temperature Ionic Liquids

Abstract: Electronic absorption spectra and Raman spectra of N,N-dimethyl-p-nitroaniline (DMPNA) have been measured in various fluids from the gaseous-like conditions in supercritical fluids (SCFs) to highly polar room-temperature ionic liquids (RTILs). We found that the S0-S1 absorption band center of DMPNA in RTILs is mostly determined by the molar concentrations of ions. On the other hand, the bandwidth of the absorption spectrum does not follow the expectation from a simple dielectric continuum model. Especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 75 publications
5
35
0
Order By: Relevance
“…The assumption that the S 1 state of 1 is essentially localized on the p-nitroaniline group is consistent with the observation of substantial analogies between the S 1 states of p-nitroaniline (PNA) 12 and N,N-dimethyl-p-nitroaniline (DPNA), 13 concerning their dynamics and spectral properties. Indeed, the S 0 -S 1 absorption band of 1 is quite comparable in shape and position to the strong S 0 -S 1 charge transfer band observed for PNA (l max 365 nm) 12 and DPNA (l max 385 nm) 13 in acetonitrile. The short-lived character of S 1 (about 1.5 ps) is also in agreement with the ultrafast S 1 decay kinetics reported for PNA (0.30 ps) and DPNA (0.63 ps) in acetonitrile.…”
Section: The Photophysical and Photochemical Behavior Ofsupporting
confidence: 78%
“…The assumption that the S 1 state of 1 is essentially localized on the p-nitroaniline group is consistent with the observation of substantial analogies between the S 1 states of p-nitroaniline (PNA) 12 and N,N-dimethyl-p-nitroaniline (DPNA), 13 concerning their dynamics and spectral properties. Indeed, the S 0 -S 1 absorption band of 1 is quite comparable in shape and position to the strong S 0 -S 1 charge transfer band observed for PNA (l max 365 nm) 12 and DPNA (l max 385 nm) 13 in acetonitrile. The short-lived character of S 1 (about 1.5 ps) is also in agreement with the ultrafast S 1 decay kinetics reported for PNA (0.30 ps) and DPNA (0.63 ps) in acetonitrile.…”
Section: The Photophysical and Photochemical Behavior Ofsupporting
confidence: 78%
“…For example, the vibrational spectrum is more sensitive to local solute-solvent interactions than the electronic spectrum, and many vibrational spectroscopy studies have been performed to investigate solute-solvent interactions in RTILs. [15][16][17][18] However, a direct comparison between the solvatochromic parameters and vibrational spectral shifts in RTILs has not been well demonstrated until now. Welton et al investigated the IR spectra of water dissolved in BMIm-cation based RTILs using ATR-IR spectroscopy and found that, relative to those in the vapor phase, both Fermi-splitting OH bands show a significant shift depending on the RTIL anion species, suggesting the existence of hydrogenbonding interactions between the water molecules and RTIL anions.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 We considered that this phenomenon is related to the local heterogeneity of the solvation in ILs, which has been studied using various experimental and theoretical methods. [6][7][8][9][10][11][12][13] In this study, we found a unique ground state reaction of DEAHF, i.e., formation of the tautomer in the ground state in specific ILs. We also found that water contamination strongly affects the equilibrium between the normal and tautomeric forms, and that there is a unique slow conversion process from the normal form to the tautomeric form in ILs.…”
mentioning
confidence: 55%
“…This is in contrast to effects of water on other probe molecules. 9 on the Raman shift in [BMIm][BF 4 ] was not significant up to 13 700 ppm. We also tested the effect of BF 4 À in a conventional liquid solvent.…”
mentioning
confidence: 95%